Swap x and y's positions
f(x) is another way of saying y, so basically tha initial function is y = 1-2x^3.
Change it up to x = 1-2y^3 and solve for y
X - 1 = - 2y^3
(X - 1)/-2 = y^3
So the cube root of ((x-1)/2) = y
So what we do is
area that remains=total area-triangle area that was cut out
we need to find 2 things
total area
triangle area
total area=rectange=base times height
area=(3x+4) times (2x+3)
FOIL or distribute
6x^2+8x+9x+12=6x^2+17x+12
triangle area=1/2 times base times height
triangle area=1/2 times (2x+2) times (x-2)=
(x+2) times (x-2)=x^2+2x-2x-4=x^2-4
so
total area=6x^2+17x+12
triangle area=x^2-4
subtract
area that remains=total area-triangle area that was cut out
area that remains=6x^2+17x+12-(x^2-4)=
6x^2+17x+12-x^2+4=
6x^2-x^2+17x+12+4=
5x^2+17x+16
area that remains is 5x^2+17x+16
Answer:
-3 3/7
Step-by-step explanation:
Hope this helps!:)
2 1/2 yds = 2.5 x 36 = 90 inches...what she started with
2 ft 8 in = 2(12) + 8 = 32 inches...what she had left
90 - x = 32
90 - 32 = x
x = 58 inches....so she used 58 inches
But baby am still catching grenade for you trow my head on a plane for you I would do anything for you